Odpowiedzi

Najlepsza Odpowiedź!
2010-02-24T16:26:22+01:00
A) 2a+3-a+6+7a
8a+9=8*(-2)+9=-7
b) 2z+t-3z+4t-1
-z+5t-1=-5+5*0,1-1=-5,5
c) 13x-2y+7-9x+y-4+x-3
5x-y=5*0,2+1=2
d) n²+n-7+3n²-n-9-n+16
4n²-n=4*(-½)²+½=1½
2010-02-24T16:28:31+01:00
2a+3-a+6+7a dla a= -2
8a +9
8*(-2) +9 =(-16)+9= (-7)


2z +t-3z+4t-1 dla =z =5 i t=0,1
(-1z)+5t-1= (-1*5)+(5*0,1)-1=(-5)+0,5 -1=(-5,5)


13x-2y+7-9x+y-4+x-3 dla- x=0,2, y=-1
5x-y(reszta się redukuje)= 5*0,2-(-1)=1+1=2


n²+n-7+3n²-n-9-n+16 dla- n-½
4n²-n=4*(½)² -½= 1-½=½



2010-02-24T16:29:34+01:00
A).2a+3-a+6+7a=a)=8a+9=8*(-2)+9=-7
b)2z +t-3z+4t-1=-1z+5t-1=-1*5+5*0,1-1=-5+0,5-1=-5,5
c) 13x-2y+7-9x+y-4+x-3=5x-1y=5*0,2-1*(-1)=1+1=2
d) n²+n-7+3n²-n-9-n+16=4n²-3n-14=4n²-n=4*(-½)²+½=1½